A polarized fast radio burst at low Galactic latitude - Petroff, E.; Burke-Spolaor, S.; Keane, E.; McLaughlin, M.; Miller, R.; Andreoni, I.; Bailes, M.; Barr, E.; Bernard, S.; Bhandari, S.; Bhat, N.; Burgay, M.; et al. (Oxford University Press, 2017)
We report on the discovery of a new fast radio burst, FRB 150215, with the Parkes radio telescope on 2015 February 15. The burst was detected in real time with a dispersion measure (DM) of 1105.6$±$0.8 pc cm^{-3}, a pulse duration of 2.8^{+1.2}_{-0.5} ms, and a measured peak flux density assuming the burst was at beam center of 0.7^{+0.2}_{-0.1} Jy. The FRB originated at a Galactic longitude and latitude of 24.66^{°}, 5.28^{°}, 25 degrees away from the Galactic Center. The burst was found to be 43$±$5% linearly polarized with a rotation measure (RM) in the range -9 < RM < 12 rad m^{-2} (95% confidence level), consistent with zero. The burst was followed-up with 11 telescopes to search for radio, optical, X-ray, gamma-ray and neutrino emission. Neither transient nor variable emission was found to be associated with the burst and no repeat pulses have been observed in 17.25 hours of observing. The sightline to the burst is close to the Galactic plane and the observed physical properties of FRB 150215 demonstrate the existence of sight lines of anomalously low RM for a given electron column density. The Galactic RM foreground may approach a null value due to magnetic field reversals along the line of sight, a decreased total electron column density from the Milky Way, or some combination of these effects. A lower Galactic DM contribution might explain why this burst was detectable whereas previous searches at low latitude have had lower detection rates than those out of the plane.